Profesionalitas Guru Ilmu Pengetahuan Sosial (IPS) di Sekolah Dasar - I.ketut P. Artana, (Pendidikan Sekolah Dasar, 2011)
The research purpose this  study were: to discribe teacher abilities of making instructional planning, actuating, evaluing, the instructions, developing  personal relationship, and to show various factor influencing their abilities in the instructional social science in the SD Lakarsantri 1 and 2 Surabaya city.Using deep interview, documentary and IPKG.Data analisys in the  field and after data collection. The result showed their abilities of planning instructions was âenoughâ  actuating it was also âenoughâ and developing relationship wasâgoodâ. Profesionalism and creativities influenced their abilities in the instruction